Chemical Investigations on the Indian Cryptomeria japonica - I. Essential Oil from the Heartwood - Bhatia, Kuldip; Lal, Jia; Ayyar, K. S. (Indian Forester, 1981)
Essential oil from the heartwood of Cryptomeria japonica was obtained by steam distillation of the petroleum ether (60-80) extract of the heartwood. Its infrared spectrum and gas-liquid chromatographic analysis indicated the presence of at least 14 compounds with hydroxyl and/or carbonyl groups. Further work on the isolation and identification of individual compound is in progress.